2000
DOI: 10.1074/jbc.m006796200
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution X-ray Crystallography Shows That Ascorbate Is a Cofactor for Myrosinase and Substitutes for the Function of the Catalytic Base

Abstract: Myrosinase, an S-glycosidase, hydrolyzes plant anionic 1-thio-␤-D-glucosides (glucosinolates) considered part of the plant defense system. Although O-glycosidases are ubiquitous, myrosinase is the only known Sglycosidase. Its active site is very similar to that of retaining O-glycosidases, but one of the catalytic residues in O-glycosidases, a carboxylate residue functioning as the general base, is replaced by a glutamine residue. Myrosinase is strongly activated by ascorbic acid. Several binary and ternary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
174
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(185 citation statements)
references
References 44 publications
6
174
0
1
Order By: Relevance
“…S6). The S. alba enzyme is thought to mediate hydrolysis by the good leaving group character of the glucosinolate aglycone and the use of the cofactor ascorbate as a base (33). The glucose recognition site is identical among the three enzymes; however, only two of the seven residues forming the aglycone binding site in plant myrosinases are identical in the P. striolata myrosinase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S6). The S. alba enzyme is thought to mediate hydrolysis by the good leaving group character of the glucosinolate aglycone and the use of the cofactor ascorbate as a base (33). The glucose recognition site is identical among the three enzymes; however, only two of the seven residues forming the aglycone binding site in plant myrosinases are identical in the P. striolata myrosinase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, myrosinases from GH family1 lack the acid/base residue. Besides that, ascorbate is a co-factor for myrosinases and replaces the catalytic base (4).…”
Section: Introductionmentioning
confidence: 99%
“…For myrosinase, it has been shown that the acid/base residue is not necessary in the first step of catalysis because of the excellent leaving group ability of the aglycone of the natural substrates (glucosinolates). For the second step, Burmeister and colleagues (24) have shown by high resolution x-ray crystallography that ascorbate is a cofactor for myrosinase and substitutes for the function of the catalytic base.…”
mentioning
confidence: 99%